Acupuntura: Histórico, bases teóricas e sua aplicação em medicina veterinária - Scognamillo-Szabó, Márcia Valéria Rizzo [UNESP]; Bechara, Gervásio Henrique [UNESP] (My University, 2010)
Acupuncture (AP) is an ancient empirical Eastern therapeutical technique that uses magical though (pre-scientific language) in this domain. Reflex therapy that uses the stimulation of specific points of the body to achieve a therapeutic or homeostatic effect. According to AP, health depends on psico-neuro-endocrine functions under the influence of the genetic code and extrinsic factors like nutrition, daily habits, weather, environment and others. The present article is a brief review on the AP philosophy, its historical marks in East and West, the veterinary AP history in Brazil and abroad. It also summarizes AP practice, including diagnosis, treatment protocols, the needling of animals, its indications, non-indications and adverse effects.
Acupuncture: History, basic principles and its use in veterinary medicine
Keywords: Adverse effects; Animals; History; Indications; Non-indications; Philosophy; Traditional chinese medicine